Real-Time Volumetric Telepresence: A Point-Cloud Overlap System with Integrated Spatial Audio - Moreira, Vitor S.; Soares, Marcos F. dos Santos; Nascimento, Hugo A. D. do; Salles, Laurita R. de (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15786, 2025)
The paper introduces a real-time volumetric telepresence system that creates a spatial overlap between a physical space and its virtual counterpart. Using an Orbbec scanner, the system captures RGB point clouds via C++ and the scanner’s SDK, transmitting data through TCP to a Node.js server. Clients visualize these point clouds using A-Frame and WebSocket connections, enabling immersive 3D interactions complemented by synchronized real-time audio. Our main contribution is a low-cost, web-based pipeline enabling precise physical–virtual overlap of live point clouds with integrated spatial audio for remote collaboration.